Country Partnership Framework for Nepal for the Period of FY2019-FY2023 - World Bank Group (World Bank, Washington, DC, 2018)
The Country Partnership Framework (CPF) covering the five-year period of FY2019-2023 comes at a time of historic transformation in Nepal. The signing of the 2006 Comprehensive Peace Agreement ended a 10-year conflictthat came at a significant cost of lives and foregone economic development. Since then, Nepal has gone through lengthy and complex transitions towards a new Constitution in 2015 that establishes a federal structure. By the end of 2017, elections were successfully held at the federal, state, and local tiers. There is a newfound optimism for greater political stability, inclusion, good governance and sustainable growth. The new federal structure presents unprecedented opportunities to reset Nepal’s development story line, as raised in the Systematic Country Diagnostic (SCD). The CPF builds on the FY2014-2018 Country Partnership Strategy (CPS) and additional analyses to identify new challenges and opportunities in the coming period. The CPF focus areas have emerged from nationwide consultations for, and analysis of the SCD.